Study of the productive characteristics of grass carp Ctenopharyngodon idella V. cultured in floating cages in the Euphrates River / Dhi-Qar Governorate - Heba M. Khudair; Kamel K. Fahd (University of Thi-Qar Journal of agricultural research, 2024)
The current study was conducted in the city of Nasiriyah / Dhi Qar Governorate, the Muhammadiyah region, with longitude and latitude coordinates 310041N" 461811E." It included measuring the environmental characteristics of the water in the study area, such as measuring temperature, turbidity, electrical conductivity, total dissolved solids, and dissolved oxygen. Samples were analyzed periodically every month and fish muscle tissues were analyzed. Grass carp at the beginning and end of culture. The study used young grass carp. 1765 fish with an average starting weight of 20-35 grams. They were distributed into three treatments with a culture density of 45, 52, and 50 fish/m3. Three floating cages made of galvanized iron were used. Dimensions of one cage (2). ,2,3) m3, An Iranian-made, floating type diet containing 32-38% protein was used for feeding. The study continued for six months, starting in October 2023 until March 2024. Fish samples were weighed every 15 days for the purpose of calculating the amount of feed provided on the basis of the weight gain, 5% of the weight. In the neighborhood, water temperatures during the study months ranged from 17-22°C, dissolved oxygen recorded between 9.33-4.3 mg/l, water electrical conductivity between 1.93-1.11 ppt, total dissolved solids between 2920-2101 mg/l, and pH value of 8.2- 7.3, The results of the study were evaluated according to growth indicators (total weight gain, daily weight gain, relative growth rate, specific growth rate, feed conversion efficiency, feed conversion rate, and protein efficiency ratio) and showed that the best results for these indicators were in the treatment with the lowest culture density. We conclude that the lower density gives the best growth indicators when adopting the culture of grass carp fish in floating cages and adopting artificial feeding with the addition of jet and aquatic plants.